2003
DOI: 10.1038/sj.onc.1207079
|View full text |Cite
|
Sign up to set email alerts
|

Sp100 is important for the stimulatory effect of homeodomain-interacting protein kinase-2 on p53-dependent gene expression

Abstract: HIPK2 shows overlapping localization with p53 in promyelocytic leukemia (PML) nuclear bodies (PMLNBs) and functionally interacts with p53 to increase gene expression. Here we demonstrate that HIPK2 and the PML-NB resident protein Sp100 synergize for the activation of p53-dependent gene expression. Sp100 and HIPK2 interact and partially colocalize in PML-NBs. The cooperation of HIPK2 and Sp100 for the induction of p21 Waf1 is completely dependent on the presence of p53 and the kinase function of HIPK2. Downregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 30 publications
2
34
0
Order By: Relevance
“…Some small HIPK2 foci remained intact and did not overlap with ZBTB4. A kinase-inactive version of HIPK2 (mutant K221A, Figure 2c) was nuclear but not recruited into foci, as published (Moller et al, 2003). This mutant protein broadly colocalized with ZBTB4.…”
Section: Identification Of Hipk2 As a Zbtb4 Interactorsupporting
confidence: 63%
“…Some small HIPK2 foci remained intact and did not overlap with ZBTB4. A kinase-inactive version of HIPK2 (mutant K221A, Figure 2c) was nuclear but not recruited into foci, as published (Moller et al, 2003). This mutant protein broadly colocalized with ZBTB4.…”
Section: Identification Of Hipk2 As a Zbtb4 Interactorsupporting
confidence: 63%
“…Several of the interferon-responsive genes under negative Notch control in keratinocytes have been previously implicated in positive growth control, apoptosis, and/or tumorigenesis (e.g., see Ghosh et al 2001;Carpten et al 2002;Wasylyk et al 2002;Zhang and Pagano 2002), with an impact that is likely to extend to keratinocytes. We note in particular the down-modulation of Sp100, a key component of nuclear bodies involved in chromatin control (Moller et al 2003), which parallels the opposite up-regulation of PML, another nuclear body component, in cells with loss of p63 expression (Bernassola et al 2005;Keyes et al 2005). While we have focused on IRF7 for direct functional studies and shown that IRF7 overexpression is sufficient to relieve Notch-dependent suppression of expression of p63, the endogenous IRF7 protein is likely to function in concert with other interferon-responsive genes in regulation of p63 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Among the suppressed genes in human cells were the ones for IRF7, a key regulator of the interferon-dependent transcription cascade with oncogenic potential (Zhang and Pagano 2002;Honda et al 2005), and Sp100, an essential component of nuclear bodies (NBs) ( Fig. 3D; Moller et al 2003), while in the mouse cells down-modulation was observed for IRF3, which physically interacts and functionally overlaps with IRF7 (Servant et al 2002), and IKK , a key kinase that positively regulates the interferon response ( Fig. 3F; Fitzgerald et al 2003).…”
Section: Notch Activation Suppresses P63 Expression Through Negative mentioning
confidence: 99%
“…Besides PML, other proteins function as cofactors for HIPK2-mediated p53Ser46 phosphorylation by binding to p53 and HIPK2. These include the PML-nuclear body components Sp100 (Moller et al, 2003b) and the death domain-associated protein Daxx (Li et al, 2007a), the p53-inducible factor p53DINP1/ TP53INP1 (Okamura et al, 2001;Tomasini et al, 2003) and Axin (Rui et al, 2004), a master scaffold for the regulation of the Wnt/b-catenin signaling pathway (Kikuchi, 1999;Peifer and Polakis, 2000) ( Figure 2). Axin (amino acids 678-753) physically interacts with HIPK2 (amino acids 935-1050) as well as p53-activating HIPK2-mediated p53Ser46 phosphorylation and facilitates p53-dependent transcriptional activity and apoptosis (Rui et al, 2004).…”
Section: Hipk2 Phosphorylates P53 At Ser46 and Mediates Apoptosismentioning
confidence: 99%